THE EVOLVING DYNAMICS OF NATIONAL SOVEREIGNTY AND POLITICS IN THE ERA OF GLOBALIZATION IN NIGERIA - Toye Manuwa (International Studies Journal)
This paper examines the changing nature of national sovereignty and politics in Nigeria in the context of globalization. It argues that globalization has both positive and negative impacts on the political and economic development of the country, as well as on its social and cultural identity. The paper analyzes the challenges and opportunities that globalization poses for Nigeria's sovereignty, democracy, security, and regional integration. It also explores the strategies and policies that the Nigerian government and civil society have adopted to cope with the effects of globalization and to enhance their participation in the global arena. The paper concludes that Nigeria needs to balance its national interests and values with its global obligations and responsibilities, and to foster a more inclusive and accountable governance system that can respond effectively to the demands and expectations of its citizens and the international community.